Modulating the Ubiquitin–Proteasome System: A Therapeutic Strategy for Autoimmune Diseases - Dhananjay Yadav; Ji Yeon Lee; Nidhi Puranik; Pallavi S. Chauhan; Vishal Chavda; Jun-O. Jin; Peter C. W. Lee (Cells, 2022)
Multiple sclerosis (MS) is an autoimmune, neurodegenerative disease associated with the central nervous system (CNS). Autoimmunity is caused by an abnormal immune response to self-antigens, which results in chronic inflammation and tissue death. Ubiquitination is a post-translational modification in which ubiquitin molecules are attached to proteins by ubiquitinating enzymes, and then the modified proteins are degraded by the proteasome system. In addition to regulating proteasomal degradation of proteins, ubiquitination also regulates other cellular functions that are independent of proteasomal degradation. It plays a vital role in intracellular protein turnover and immune signaling and responses. The ubiquitin–proteasome system (UPS) is primarily responsible for the nonlysosomal proteolysis of intracellular proteins. The 26S proteasome is a multicatalytic adenosine-triphosphate-dependent protease that recognizes ubiquitin covalently attached to particular proteins and targets them for degradation. Damaged, oxidized, or misfolded proteins, as well as regulatory proteins that govern many essential cellular functions, are removed by this degradation pathway. When this system is affected, cellular homeostasis is altered, resulting in the induction of a range of diseases. This review discusses the biochemistry and molecular biology of the UPS, including its role in the development of MS and proteinopathies. Potential therapies and targets involving the UPS are also addressed.